Mitochondrial complex deficiency by novel compound heterozygous TMEM70 variants and correlation with developmental delay, undescended testicle, and left ventricular noncompaction in a Japanese patient: A case report. Issue 3 (7th February 2019) - Hirono, Keiichi; Ichida, Fukiko; Nishio, Natsuhito; Ogawa‐Tominaga, Minako; Fushimi, Takuya; Feichtinger, Rene′ G.; Mayr, Johannes A.; Kohda, Masakazu; Kishita, Yoshihito; Okazaki, Yasushi; Ohtake, Akira; Murayama, Kei
Key Clinical Message: We identified novel compound heterozygous TMEM70 variants in a Japanese patient who had hyperlactacidemia, metabolic acidosis, hyperalaninemia, developmental delay, undescended testicle, and left ventricular noncompaction. The urinary organic acids profile revealed elevated levels of 3‐MGA, and BN‐PAGE/Western blotting analysis and ETC. activity confirmed complex V deficiency. Abstract : We identified novel compound heterozygous TMEM70 variants in a Japanese patient who had hyperlactacidemia, metabolic acidosis, hyperalaninemia, developmental delay, undescended testicle, and left ventricular noncompaction. The urinary organic acids profile revealed elevated levels of 3‐MGA, and BN‐PAGE/Western blotting analysis and ETC. activity confirmed complex V deficiency.